Newly developed biocarbon to increase electrical conductivity in sustainable polyamide 12 composites. Issue 11 (10th September 2022) - Das, Chinmoyee; Tamrakar, Sandeep; Mielewski, Debbie; Kiziltas, Alper; Xie, Xinfeng
Abstract: Sustainable manufacture caused shift in automotive manufacturing practices. Polymer‐based composites make up almost 15% mass of the entire vehicle, most importantly the fuel system of the vehicle. Poor electrical conductivity of the polymer composites leads to electrostatic deposition, which can lead to issues. Carbon based synthetic fillers like carbon fiber and carbon nanotubes are attractive options to develop electrically conductive composites, owing to their excellent electrical and mechanical properties. However, the production process of these reinforcements is highly time and energy intensive making it quite expensive and not quite sustainable. Lignocellulosic feedstock can be carbonized at a high treatment temperature of ≥1000°C to produce electrically conductive biocarbon filler. In this study biocarbon fibers developed using Douglas fir pulp, were incorporated into polyamide 12 matrix to develop composites. The composites were fabricated using hot compression mounting. At a filler loading of 7.5 wt% the composites reported log electrical conductivity value of −6.67 S/cm and at 35 wt% filler loading rate the composite conductivity was −0.31 S/cm. An electrical conductivity of −8.70 S/cm for polyamide 6 composites filled with 20 wt% carbon fiber and −1.03 S/cm were reported for 40 wt% carbon fiber concentration in reviewed literature. The electrical conductivity values for the samples with 20 and 40 wt% carbon fibers are significantly lower compared to the biochar fiber filled composites at 25 and 35 wt% biochar filler loading rates, indicating the effectiveness of the biochar filler as a conductive filler in developing electrically conductive, sustainable composites. Abstract :